Recurrent Stroke-Like Symptoms After Cesarean Section Deliveries in a Female Patient With X-Linked Charcot-Marie-Tooth Type 1 - Li, Qu; Chen, Chen; Ren, Yan; Liu, Xu (Frontiers in Neurology, 2020)
Background: X-linked Charcot-Marie-Tooth type 1 (CMTX1) is the second most frequent form of CMT, which is caused by mutations in the gap junction beta 1 gene (GJB1) coding for connexin 32 protein. In addition to typical peripheral neuropathy, central nervous system (CNS) involvement in patients with CMTX1 has been reported as a special feature, but female patients are rarely affected. Case presentation: We describe a 29-year-old female who had a history of two cesarean deliveries. After each delivery, she presented transient and recurrent slurred speech and limb weakness. Magnetic resonance imaging (MRI) showed diffuse abnormal signals in the corpus callosum, posterior limbs of bilateral internal capsule, and centrum semiovale. Electromyogram showed sensorimotor peripheral neuropathy with the characteristics of intermediate CMT. The C.622G>A mutation (p.Glu208Lys) in the GJB1 gene was detected by PCR-sequencing. Conclusion: The diagnosis of CMTX1 should be considered, even in female patients, when the disease presents with recurrent stroke-like symptoms and abnormal white matter signals on MRI. The puerperium after delivery may be one of the precipitating factors.